Gambaran Pelaksanaan Pembelajaran Pendidikan Jasmani Adaptif Untuk Anak Autis Tingkat Sekolah Menengah Pertama Pada Sekolah Khusus - Hafizin, Haerul; Fitriatun, Erna (CV Insan Kreasi Media, 2024)
Adaptive physical education learning is important for children with autism. However, the process of implementing adaptive physical education learning in special schools SLB Negeri 2 Mataram is only carried out by one physical education teacher while the number of classes from kindergarten, elementary, junior high and high school levels is very large. Moreover, the physical education learning process carried out by physical education teachers is only assisted by class teachers who are not from the field of physical education. The incompatibility of lesson plans with the learning carried out also requires physical education teachers to be more active in providing learning. The purpose of this study was to determine the implementation of adaptive physical education learning for children with autism in special schools SLB Negeri 2 Mataram. This research uses a qualitative descriptive method approach. The subjects in this study were physical education teachers, class teachers and principals. Data collection techniques using observation, interviews and documentation. Data analysis techniques using qualitative descriptive analysis with steps of reduction, data display and conclusion drawing (verification). The results showed that adaptive physical education learning in SLB Negeri 2 Mataram special school was in accordance with the objectives of adaptive physical education, namely improving the cognitive quality and independence of autistic students through children's motor development activities. Learning activities have covered most of the needs of students although teachers have to work harder due to the large number of students. The process of assisting autistic students in learning is also carried out by physical education teachers who collaborate with class teachers to create a conducive atmosphere during learning.